Beyond 'La baguette et le fromage': Studying minority francophone culture and community in western Canada. - Veresovaya, Natalya (Author); Bouchard, Michel (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2010)
The question of French language rights has been continuously discussed in the Canadian State. In 1982 the Canadian constitution and Article 23 of the Canadian Charter of Rights and Freedoms guaranteed French students to receive primary and secondary education in that language. This research examines whether an elementary FFL school in Peace River, Alberta, produces a positive impact on French identity and culture. It also studies how francophone teachers and students define and construct French identity on a daily basis. In order to complete this study qualitative methods (participant observation, informal and formal interviews, questionnaires, and participatory action research) were used. The results indicate that an elementary FFL school of Peace River has succeeded in promoting positive attitudes to French language and culture and that extracurricular activities can reinforce this effect. This research demonstrates that students have more positive opinions of French language and culture once they have participated in a French cultural activity. Francophone students use the French language when they are in a FFL school and sometimes when they are among anglophones. L’École Des Quatre Vents and its teachers has become an effective tool in constructing French identity and a sense of belonging for a French-speaking community among a young generation of francophones. The status of French language has improved, whereas in the past it was stigmatized. This study reveals that education in French language helps students articulate and understand their culture better in the minority context of the Peace River region, Alberta. --P. i. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1754813